Revitalisasi Kegiatan Keagamaan Masa Pandemi Covid 19 Dengan Pengajian Keliling Di Sdi Miftahul Qulub Polagan - suhaimi; Mohammad Fahrur Rozi (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2022)
In order to increase religious values ​​in schools, it is necessary to hold religious activities. Religious activities are described based on the Government Regulation of the Republic of Indonesia Number 55 of 2007 concerning Religious Education and Religious Education and the National Education System Article 3 No. 20 of 2003, national education functions to develop capabilities and shape the character and civilization of a dignified nation in the context of educating the nation's life, aiming at developing the potential of students to become human beings who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable. , creative, independent, and become a democratic and responsible citizen.” Therefore, religious activities must be formed and implemented in order to achieve the goals of national education. Given the unfinished covid-19 pandemic and education has entered the new normal, so that religious activities run optimally but by complying with health protocols, it is necessary to revitalize religious activities. Revitalization is an update step in previous activities so that students return to remembering tahlil readings, prayers and prayers that have not been done for a long time due to the lockdown. One of the steps to revitalize religious activities at SDI Miftahul Qulub Polagan is to conduct a recitation of hadrah banjari tours. KeyWord: Revitalization, Religion, recitation